(3QhLjI ZGQhOj jbGVj GdUgjhfjI GdESQGFjdjIs - (3ZGQhOj, QhLjIs 1913-; (3HhfGUja, QGfjGs; (3QjTG, HjGQs; (3RZjH, gfQjs ((3HjQhJs (3YhjOGJ ddfTQ h GdWHGYIs, 2000)
(3COjf ZGQhOj HYO eMGceJg aj aQfSG HSHH cJGHg (B"(3GdCSGWjQ GdeDSSI ddSjGSI GdESQGFjdjI(B" (3HJgeJjf GdChdi(B: (3bOM CaQGO hLeGYGJ HSHH GfJeGFge GdBJfj Ch GdOjfj(B. (3hGdKGfjI GdJbdjd ef aOGMI LQGFe gJdQ(B. (3EdG Cf ZGQhOj hHGdfSHI dQqOg Ydi GdJgeI GdChdi jbhd HCfg jJMOi CjkG cGf Cf jLO aj cJGHg SWQkG hGMOkG GSJNOe ajg cdeI (B"(3jghOj(B" (3HeYfi JMbjQj(B. (3hjbhd HCfg GfJbO abW ef GSJNOehG GdOjf (B((3CaQGOkG Ce CMRGHkG(B) (3dJHQjQ SjGSJge(B. (3agh hEf COGf SjGSI MRH WGdHGf, agPG dG jYfj Cfg Pqe GdESdGe, Hd GdYcS jchf HPdc bO OGaY Yf GdESdGe VqO ef dG jTQahfg(B. (3haj gPG GdefMi, jJGHY ZGQhOj, Cfg hYfO GfJbGOg ddeJTOOjf GdESQGFjdjjf Ch efGUQjge (B((3HSHH JSNjQge GdOjGfI aj NOeI SjGSI MQH(B) (3Jchf eYQcJg VOge Vef eYQcJg VO efGgVI GdSGejI GdJj jHfhf ge SjGSJge Ydi EWdGbgG, hgh jYJHQgG LQjeI jYGbH YdjgG GdbGfhf(B. (3CeG HGdfSHI ddJgeI GdKGfjI GdehLgI Edjg(B: (3GdJbdjd ef aOGMI LQGFe gJdQ jbhd HCf CYOGAg ge GdPjf jbddhf ef aXGYJgG YHQ(B: (3C(B-(3MUQge gPg GdLQGFe HJdc GdJj GQJcHgG gJdQ VO GdjghO hMOge aj Mjf cdaJ MQH gJdQ (B50 (3edjhf bJjd(B. (3H(B-(3JQcjRge MUQjkG Ydi hGMO abW Ohf ShGg ef CSGdjHg aj GdbJd hJSJQge Ydi CTcGd CNQi YOjOI ef LQGFeg(B. (3gPG ef fGMjI(B. (3hef fGMjI KGfjI jdbj ZGQhOj HYV GdVhA Ydi HYV eG LGA HYO GdeMGceI ef QOhO aYd MjK SCdg (B"(3jghOj efMjf(B" (3hYfOeG bQC fU GdMce GdPj gh HUOO GSJFfGag, SCdg, cja LQJ LdSGJ gPg GdeMGceI GdYHKjI? hjbhd ZGQhOj HCf (B"(3jghOj efhMjf(B" (3h(B"(3gh ehSjbj cHjQ(B" (3de jcf GdhMjO GdPj QaV YHKjI GdMce, aQFjS LeghQjI ShjSQG GdSGHb (B((3GdeDQN CUdkG(B) (3GdSjO ThaGdGR hUa gPg GdOYhi HGd`(B"(3eGcGQJjRejI GdLOjOI h(B"(3eWGQOI GdSGMQGJ(B" (3eJMOKkG Yf JMbjb bVGFj(B. (3haj LQjOI (B"(3SJGeHG(B" (1998/3/28) (3GYJQV Ydi GdMce eLehYI CSGJPI ef CcHQ LGeYGJ EjWGdjG hGUajf eMGceI ZGQhOj Ydi cJGHg (B"(3GdCSGWjQ GdeDSSI ddSjGSI GdESQGFjdjI(B" (3HCfgG JTcd aUdkG NWjQkG ef GdbeY GdKbGaj, hJcTa Yf NWQ GdLfhM Edi GdJNda hHQHQI GdefGN GdKbGaj aj ChQhHG, hCf jMce Ydjg dCfg, eSJfOkG Edi JhKjb hGSY eSJelO ZGdHkG ef cJGH jghO, fGbT hCYGO EHQGR GdBdjI GdeJhMTI GdJj SHHJ eG GYJHQg (B"(3GSJTgGO GdjghO(B"(3, hGdLQGFe GdTfjYI GdJj GQJcHgG gJdQ VO GdjghO, hjVja gDdGA GdCSGJPI HCfge jMHPhf efGbTI MQI dfXQjGJ ZGQhOj, hjMJLhf Ydi Mce MQjI GdQCj gPG hYdi GdbGfhf GdPj ChMi Hg bGfhf (B"(3ZjSh (BGayssot" (3ceG jYHQhf Yf Nhage ef GdCNWGQ GdJj JgOO GdKbGaI hGdfTQ dG aj aQfSG hMSH Hd aj cd ChQhHG, EPG GfJTQJ aj GdeMGce ehLI GdMdhd acGf eG jecf Cf jYGdL HGdHMK GdYdej(B. (3hjbhd ZGQhOj Cfg CSYOg gPG GdGSJFfGa GdPj bOeg hCYOGAg aj Bf hGMO, dCf GdCMOGK, CKHJJ fXQjJg Mhd GdCNWGQ GdfGLeI Yf TQM eJTOO ddcJGH hddJGQjN, hYf JMhjd GdCSWhQI JGQjNkG hGbYkG(B. (3hjVja ZGQhOj HCf eG Hbj ef GdeMGceI GdChdi, GdeSJeOI ef bGfhf ZGjSh, Cf nHognJ nCndob aQfSG ehWfkG dMbhb GdEfSGf hMQjI GdJYHjQ, heG jbhe Hg ef NdGd UaMGJ gPG GdcJGH GdPj jbGVj ajg GdUgjhfjI GdESQGFjdjI HJfGhdg GdSjGSI GdESQGFjdjI hCSSgG GdCjOjhdhLjI (B((3hGdPj jYJHQg HeKGHI GSJFfGa ddMce(B) (3jJefGg jQee eG dMb HUhQI aQfSG ef VQQ ef NdGd eMGceJg Ydi cJGHg (B"(3GdCSGWjQ GdeDSSI ddSjGSI GdESQGFjdjI(B"s
1
Keywords: (3GdUgjhfjIs; (3GdjghOjIs; (3ESQGFjds -- (3JGQjNs